2016
DOI: 10.3310/hta20430
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the clinical effectiveness and cost-effectiveness of pharmacological and psychological interventions for the management of obsessive–compulsive disorder in children/adolescents and adults

Abstract: BackgroundObsessive–compulsive disorder (OCD) is a relatively common and disabling condition.ObjectivesTo determine the clinical effectiveness, acceptability and cost-effectiveness of pharmacological and psychological interventions for the treatment of OCD in children, adolescents and adults.Data sourcesWe searched the Cochrane Collaboration Depression, Anxiety and Neurosis Trials Registers, which includes trials from routine searches of all the major databases. Searches were conducted from inception to 31 Dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(78 citation statements)
references
References 246 publications
2
74
0
2
Order By: Relevance
“…Previous studies have shown the comorbidity between OCD, alexithymia, and anxiety or depression [14][15][16][17]. For example, a study [18] in Finland with a large sample size (> 2,000) reported that compared to type A alexithymia (characterized by significantly higher scores in DDF and externally oriented cognitive style), type B alexithymia (characterized by significantly higher scores in DIF) was associated with a higher prevalence of self-reported diagnosis of major depressive disorder (30.2 vs. 8.3%) and anxiety disorder (18.9 vs. 3.3%).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown the comorbidity between OCD, alexithymia, and anxiety or depression [14][15][16][17]. For example, a study [18] in Finland with a large sample size (> 2,000) reported that compared to type A alexithymia (characterized by significantly higher scores in DDF and externally oriented cognitive style), type B alexithymia (characterized by significantly higher scores in DIF) was associated with a higher prevalence of self-reported diagnosis of major depressive disorder (30.2 vs. 8.3%) and anxiety disorder (18.9 vs. 3.3%).…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive behavioral therapy is a form of psychotherapy, which is flexible, individualized and can be adapted to a wide range of individuals and a variety of settings. Worldwide, it has been successfully applied in various psychiatric ailments like depression, anxiety, obsessive-compulsive disorder, phobias and eating disorders [16][17][18]. It has also been used as an adjunct to the existing therapy in various chronic diseases (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining 14 meta-analyses included patients with treatment-respondent OCD. Of these 14 studies, 6 were about double-blind, randomized, placebo-controlled trials on pediatric patients with OCD that showed superiority of SRIs for the treatment of OCD with a moderate effect size and a non-significant risk of suicidality, as well as that combined therapy was no more effective irrespective of the initial severity of the samples [14,[45][46][47][48][49]. All meta-analyses found that high doses of SSRIs were more effective as first-line therapy for patients with OCD; however, combined therapy was more effective than monotherapy.…”
Section: Evidencementioning
confidence: 99%